Sixteen New Cases Contributing to the Characterization of Patients with Distal 22q11.2 Microduplications - Wincent, J. (S. Karger AG, 2011)
The chromosome region 22q11.2 has long been recognized to be susceptible to genomic rearrangement. More recently, this genomic instability has been shown to extend distally (involving LCR22E–H) to the commonly deleted/duplicated region. To date, 21 index cases with ‘distal’ 22q11.2 duplications have been reported. We report on the clinical and molecular characterization of 16 individuals with distal 22q11.2 duplications identified by DNA microarray analysis. Two of the individuals have been partly described previously. The clinical phenotype varied among the patients in this study, although the majority displayed various degrees of developmental delay and speech disturbances. Other clinical features included behavioral problems, hypotonia, and dysmorphic facial features. Notably, none of the patients was diagnosed with a congenital heart defect. We found a high degree of inherited duplications. Additional copy number changes of unclear clinical significance were identified in 5 of our patients, and it is possible that these may contribute to the phenotypic expression in these patients as has been suggested recently in a 2-hit ‘digenic’ model for 16p12.1 deletions. The varied phenotypic expression and incomplete penetrance observed for distal 22q11.2 duplications makes it exceedingly difficult to ascribe pathogenicity for these duplications. Given the observed enrichment of the duplication in patient samples versus healthy controls, it is likely that distal 22q11.2 duplications represent a susceptibility/risk locus for speech and mild developmental delay.